EFEKTIVITAS LAYANAN KELUHAN DAN RATING KONSUMEN TERHADAP KEPUASAN PELANGGAN SHOPEE INDONESIA - Lasmini, Ayu Dwi; Azhar, Andi (UM. Bengkulu, 2025)
This study aims to analyze the influence of complaint services and consumer ratings on customer satisfaction by considering the mediating role of affective commitment. Data were obtained from respondents in Bengkulu Province and analyzed using the Structural Equation Modeling (SEM) method with AMOS software. The results of the study showed that the complaint service had a positive but not significant influence on customer satisfaction. This means that these service improvements do not directly improve customer satisfaction. In contrast, consumer ratings have a negative but significant influence, indicating that a less transparent rating system can lower customer satisfaction. Affective commitment has been shown to have a significant effect on customer satisfaction, but does not mediate the relationship between complaint service and consumer ratings on customer satisfaction. These findings indicate that Shopee needs to improve the transparency and reliability of its rating system, as well as improve its complaint service to be more responsive and effective. With a better strategy, Shopee can increase customer satisfaction and strengthen user loyalty. Keywords: Customer Satisfaction, Complaint Service, Consumer Rating, Affective Commitment, Shopee.